FORMATION OF TRADITIONAL POTTERY SCHOOLS AND THEIR CHARACTERISTICS (American Journal of Pedagogical and Educational Research, 2022)
At the beginning of the 21st century, special attention has been paid to the preservation and development of national craft traditions and to the proper promotion of the work of folk craftsmen. Handicrafts are an integral part of our national values, and this type of activity inherited from our ancestors has developed further in the years of independence. A number of works are being carried out to restore and develop the traditions of hand-making ceramic products of our ancestors, some of which are about to be forgotten, and to create works of art from ordinary clay.